A Risk Assessment Score and Initial High‐sensitivity Troponin Combine to Identify Low Risk of Acute Myocardial Infarction in the Emergency Department. - Pickering, John W.; Flaws, Dylan; Smith, Stephen W.; Greenslade, Jaimi; Cullen, Louise; Parsonage, William; Carlton, Edward; Mark Richards, A.; Troughton, Richard; Pemberton, Christopher; George, Peter M.; Than, Martin P. (Academic Emergency Medicine, 2018)
Abstract: Objectives: Early discharge of patients with presentations triggering assessment for possible acute coronary syndrome (ACS) is safe when clinical assessment indicates low risk, biomarkers are negative, and electrocardiograms (ECGs) are nonischemic. We hypothesized that the Emergency Department Assessment of Chest Pain Score (EDACS) combined with a single measurement of high‐sensitivity cardiac troponin (hs‐cTn) could allow early discharge of a clinically meaningful proportion of patients. Methods: We pooled data from four patient cohorts from New Zealand and Australia presenting to an emergency department with symptoms suggestive of ACS. The primary outcome was major adverse cardiac events (MACE) within 30 days of presentation. In patients with a nonischemic ECG we evaluated the sensitivity for MACE and percentage low risk of every combination of high‐sensitivity cardiac troponin T (hs‐cTnT) concentration and high‐sensitivity cardiac troponin I (hs‐cTnI) concentration with EDACS. We used a standard smoothing technique on the probability density function for hs‐cTn and EDACS and applied bootstrapping to determine the optimal threshold combinations, namely, the combination that maximized the percentage low risk with ≥98.5% sensitivity for MACE. Results: From 2,536 patients, 2,258 presented without an ischemic ECG of whom 272 (12.1%) had a MACE within 30 days. The optimal threshold for hs‐cTnI was 7 ng/L combined with an EDACS threshold of 16 (36.8% patients low risk). The optimal thresholds for hs‐cTnT were 8 ng/L combined with an EDACS threshold of 15 (30.2% patients low risk). Conclusion: Single measurements of both hs‐cTnI and hs‐cTnT at presentation combined with EDACS to identify over 30% of patients as low risk and therefore eligible for safe early discharge after only one blood draw.